Placental Histopathological Examination in Foetal Sepsis - Nur Syahrina Rahim; Haza Syakirin Mohamad Zin; Salmi Abdullah; Norazlah Bahari; Vijayaletchumi Thandayathany; Abd Rahman Hayati (Universiti Malaysia Sabah, 2024)
Case Report